Oxygen Defect Engineering of β‐MnO2 Catalysts via Phase Transformation for Selective Catalytic Reduction of NO. Issue 43 (1st August 2021) - Yang, Runnong; Peng, Shaomin; Lan, Bang; Sun, Ming; Zhou, Zihao; Sun, Changyong; Gao, Zihan; Xing, Guichuan; Yu, Lin
Abstract: The catalysts for low‐temperature selective catalytic reduction of NO with NH3 (NH3 ‐SCR) are highly desired due to the large demand in industrial furnaces. The characteristic of low‐temperature requires the catalyst with rich active sites especially the redox sites. Herein, the authors obtain oxygen defect‐rich β‐MnO2 from a crystal phase transformation process during air calcination, by which the as‐prepared γ‐MnO2 nanosheet and nanorod can be conformally transformed into the corresponding β‐MnO2 . Simultaneously, this transformation accompanies oxygen defects modulation resulted from lattice rearrangement. The most active β‐MnO2 nanosheet with plentiful oxygen defects shows a high efficiency of > 90% NO conversion in an extremely wide operation window of ≈120–350 °C. The detailed characterizations and density functional theory (DFT) calculations reveal that the introduction of oxygen defects enhances the adsorption properties for reactants and decreases the energy barriers of *NH2 formation more than 0.3 eV (≈0.32–0.37 eV), which contributes to a high efficiency of low‐temperature SCR activity. The authors finding provides a feasible approach to achieve the oxygen defect engineering and gains insight into manganese‐based catalysts for low‐temperature NO removal or pre‐oxidation. Abstract : Oxygen defect‐rich β‐MnO2 nanosheet and nanorod are obtained from a crystal phase transformation based on γ‐MnO2 lattice rearrangement during a facile air calcination method. The most active β‐MnO2 nanosheet with plentiful oxygen defects shows a high efficiency in an extremely wide operation window in selective catalytic reduction of NO with NH3, which provides a new approach for catalyst engineering.